On univocal connectives - Ertola Biraben, Rodolfo Cristian (2009)
We pay attention to the concept of univocal connective. Considering the corresponding definition in the context of the sequent calculus a problem arises in a paper by Belnap. We provide an explanation by Belnap and finally give some examples and non-examples of univocal connectives.
Keywords: Univocal connectives; Non-classical logics